Clinical Pattern of Neck Pain among the Patients Attending in the Department of Physical Medicine, Bangabandhu Sheik Mujib Medical University (BSMMU), Dhaka - Shakoor, MA; Hasan, Suzon Al; Mian, M Anwarul Huq; Khan, S Zaman; Moyeenuzzaman, M; Islam, MQ (TAJ: Journal of Teachers Association, 2009)
A study was conducted in the Department of Physical Medicine, BSMMU, during the period of June 1996 to March 1997 to find out the clinical patterns of neck pain and their causes. A total of 6476 patients attended the department of which 1360 (21.01%) patients presented with neck pain. Male and female ratio was 1:0.83. Highest number of patients was in the 40-49 years age group (41.44%). In respect to occupation, table workers constituted the majority (26.08%). Most of the patients (79.64) were diagnosed as cervical spondylosis. By these findings we can conclude that the cervical spondylosis is the commonest pattern of presentation of neck pain in the Department of Physical Medicine, BSMMU, Dhaka, Bangladesh. doi: 10.3329/taj.v15i2.3912 TAJ December 2002; Vol.15(2): 74-77